Synergistic Effect of Pericarp of Mangosteen and Propolis from Stingless Bee Extracts on Nitric Oxide Scavenging Activity - Imron Meechai; Rokeeyah Suha; Nurihan Daleng; Isma-ae Chelong; Acharee Suksuwan (Journal of Tropical Pharmacy and Chemistry, 2023)
The aim of this research is to study the synergistic effect on the nitric oxide scavenging activity of mangosteen pericarp and the stingless bee (Tetragonula laviceps) propolis extracts and their phytochemical constituents. The propolis and mangosteen pericarp were extracted by reflux method with ethanol. TPC and TFC of propolis extract were 123.73±2.80 mg GAE/g extract and 70.65±11.21 mg QE/g extract, respectively, and mangosteen pericarp extract was 387.93±15.10 mg GAE/g extract and 87.00±5.06 mg QE/g extract, respectively. The ESI-LC-MS data displayed that both extracts have a variety of phytochemical constituents, such as xanthones, flavonoids, and miscellaneous. The synergistic effect of Nitric oxide scavenging activities of propolis and mangosteen pericarp extracts showed higher activity than individual extracts with various concentrations. Thus, the synergistic effect of propolis and mangosteen pericarp extracts may be an alternative source of inflammatory drug development in the future.